2014
DOI: 10.1016/j.bpj.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Smooth DNA Transport through a Narrowed Pore Geometry

Abstract: Voltage-driven transport of double-stranded DNA through nanoscale pores holds much potential for applications in quantitative molecular biology and biotechnology, yet the microscopic details of translocation have proven to be challenging to decipher. Earlier experiments showed strong dependence of transport kinetics on pore size: fast regular transport in large pores (> 5 nm diameter), and slower yet heterogeneous transport time distributions in sub-5 nm pores, which imply a large positional uncertainty of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 115 publications
6
93
0
Order By: Relevance
“…Power spectral density plots shown in Figure 4b for different applied voltages in range 0–200 mV show that the noise is comparable to nanopores in SiN x membranes at this bandwidth. 35 Both pores exhibit typical 1/ f noise regions that decrease with frequency until overwhelmed by capacitive noise at f > 10 4 Hz, which is dampened using the 200 kHz digital low-pass filter (shoulders on right). The 1/ f noise in our MoS 2 membranes is atypical of 2D pores.…”
Section: Resultsmentioning
confidence: 99%
“…Power spectral density plots shown in Figure 4b for different applied voltages in range 0–200 mV show that the noise is comparable to nanopores in SiN x membranes at this bandwidth. 35 Both pores exhibit typical 1/ f noise regions that decrease with frequency until overwhelmed by capacitive noise at f > 10 4 Hz, which is dampened using the 200 kHz digital low-pass filter (shoulders on right). The 1/ f noise in our MoS 2 membranes is atypical of 2D pores.…”
Section: Resultsmentioning
confidence: 99%
“…This result seems counterintuitive regarding the literature [26]. Indeed, it was commonly reported an increase of the dwell time with the length of the DNA strands [15]. Thus, this point should be clarified.…”
Section: Resultsmentioning
confidence: 72%
“…As previously mentioned, DNA detection is commonly performed by SiN nanopore. The latter is limited for the detection of DNA strand with more or less Carson and co-worker [15] have successfully detected dsDNA 35 bp using a high resolution amplifier with a dwell time close to 10 μs. In the case of graphene nanopore, the dwell time for DNA 25 bp is 12.5 μs [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the typical velocity in biological pores and solid-state nanopores with comparable diameter is on the order of 1 nt or bp per ls. 174,188 Other difficulties limiting the sensitivity of the measurements are the random thermal motion of DNA within the pore, The demands for parallelization of the nanopore readings are indeed high, since a single nanopore working at 10 ms/bp would take about 20 years to sequence a human genome. 200 In order to achieve the required high-throughput parallelized sequencing, Huang et al 201 recently demonstrated that it would be feasible to replace electric current measurements with fluorescence imaging of the ionic current through the nanopores.…”
Section: Physics Of Confined Dna: From the Odijk To The De Gennes Regimementioning
confidence: 99%